The influence of nitrogen and titanium carbonitride particles on structure and properties of metal Fe-C-Cr-Ni-Mo system deposited by flux wire - G. N. Sokolov; A. A. Artemev; Yu. N. Dubtsov; E. N. Eremin; V. B. Litvinenko-Ar’kov; A. S. Losev (Омский научный вестник)
The influence of nitrogen and titanium carbonitride particles on the structure and properties of high-chromium steel deposited by flux cored wire has been studied. It has been shown that the quality formation of the deposited metal and pore absence in it are achieved with nitrogen concentration in wire filler no more than 0,32 WT %. It has been found that in adding titanium carbonitride particles from 0,2 to 0,6 WT % to wire filler the effect of deposited Fe-C-Cr-Ni-Mo-N system metal modification is implemented and its operational properties increase. The developed flux cored wire has been recommended for oil and gas equipment surfacing.